PELAKSANAAN PRINSIP TANGGUNG JAWAB TERBATAS DIREKSI ATAS UTANG PAJAK PERSEROAN DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 41/PUU-XVIII/2020 - Tobing, Novalina Magdalena Boru Tobing; Anthon Nainggolan; Poltak Siringoringo (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Insolvent verdict that given to the company makes the company lose its legal status so that the Board of Directors no longer has the right to manage the company, as well as their obligations. Taxes are payable at the time of transaction and taxes have a special nature in the form of prior rights to be paid even when the company is insolvency and the company’s assets are not sufficient to pay off these obligations. The objective of this study is how the application of Director limited liability on the Limited Liability Company and how is the certainty of Director limited liability on the Decision of the Constitutional Court of the Republic of Indonesia Number. 41/PUU-XVIII/2020? The research method used is qualitative, with a statutory approach, and data collection is carried out through case studies. The data used are secondary data in the form of primary legal materials: decisions of the Constitutional Court, the Law on Limited Liability Companies, the Insolvency Law and Tax Law, while secondary legal materials are obtained from books and other literature, tertiary legal materials in the form of dictionaries, then the collected legal materials were compiled and analyzed.The results of this study indicate that even though the company has been declared insolvent, if the tax payable existed before the insolvency condition, the Directors at that time are still responsible to paid even to their personal assets.